The implementation of data mining technology in tourism industry - Siti Aishah @ Tsamienah, Taib; Noratikah, Abu; Azlyna, Senawi (AIP Publishing, 2024)
Data analytic approach has been widely used in combining with the traditional method in order to improve the accuracy of forecasting, especially in tourism industry. Currently, the common used approach is known as data mining technology, which can dramatically accelerate the recovery process of the tourism industry after the outbreak of COVID-19. The purpose of this paper is to review the implementation of data mining technology in tourism industry based on different case studies that were collected through selected digital databases. Based on the literature reviews, there is no doubt that data mining technology has the potential to be extremely important in tourism research. This technology can help the industrial practitioners make wise decision in future since it provides an efficient approach for identifying and comprehending customer behavior’s pattern. It is hoped that this study can contribute as a reference for the future studies and are able to help destinations and tourism businesses maintain continuous supplies of tourism products and services in order to fulfill the customer’s demand.